Keanekaragaman dan Kelimpahan Gastropoda di Pantai Selatan Gunungkidul Yogyakarta - Dian Kusuma Wardani; Najda Rifqiyati (Bioveritas Journal of Biology, 2022)
The South Coast of Gunungkidul has beaches that have a diversity of marine life, especially gastropods. The high number of tourists and the existence of community activities that utilize marine life may disrupt the sustainability of the ecosystem on the coast. The aims of this study are the diversity, abundance, level of diversity, evenness, and environmental factors that influence them. The research was conducted at Ngobaran Beach, Nguyahan Beach, and Watu Kodok Beach in May-August 2016. Data were collected using the quadratic method with a total of 75 plots (3 times). Based on the research found 13 families of 36 species. 5 species were frequently appeared in three locations, namely M. granulata, M. literate, M. paupercula, C. coronatus, and C. matriculates, the most abundant of which was M. granulata (Ngobaran Beach: 160 ind/75 m2; P. Nguyahan: 82 ins/75 m2; Watu Kodok Island: 36 in/75 m2). The level of diversity was moderate (Ngobaran Island: 1.73; Nguyahan Island: 2.35; Watu Kodok Island 2.65) and the evenness level was fairly even-almost evenly (Ngobaran Island: 0.60; Nguyahan Island: 0.60). 0.76, P. Watu Kodok: 0.86). Based on the results of the analysis of the relationship between environmental factors and gastropods using CCA, 4 groups were found. Group 1 consisted of 10 species affected by salinity. Group 2 consists of 5 which are affected by water temperature. Group 3 consisted of 11 species affected by COD, BOD, and DO. Group 4 consisted of 10 species that were not affected by the measured parameters. Based on the results, it can be concluded that the diversity of gastropods on the three beaches is moderate.